Synthesis and characterization of cis-bisdiphenylphosphinoethene gold(I) complexes - Fayet, Océane Yvonne Odette; Crespi, Stefano; Orthaber, Andreas (Comptes Rendus. Chimie)
A series of solid-state structures of gold(I) complexes using the semi-rigid cis-1,2- bis(diphenylphosphino)ethene (= cis-bdppe) ligand are reported. The proximity of the phosphine donor atoms of the bidentate ligand framework greatly favors formation of mononuclear over di- nuclear complexes. Structural analysis and theoretical studies shed further light on counter intermolecular packing motifs in the solid state including interactions of solvent, ligand and counterion fragments.